Reducing the risk of and the severity of the consequences of accidents during elevator accidentsReducing the risk of and the severity of the consequencesof accidents during elevator accidents - Panfilov A.V.; Kolganov V.P.; Bahteev O.A.; Apryshkin D.S.; Chauzov V.V. (Научно-технический вестник Брянского государственного университета)
This study examines the safety issues associated with the operation of elevator equipment, the causes of accidents during accidents, and suggests ways to reduce the severity of their consequences. A prerequisite for applying a risk-based approach in control and supervisory activities is the collection, systematization and analysis of information on the state of technical devices in order to assess the risk of incidents on them to ensure safe operation and reduce the administrative burden associated with inspections at facilities where the risk is minimal. The aim of the study is to develop ways to reduce the risk of accidents with personal injury or death at elevator structures and the severity of their consequences. The study used statistical data on the number of accidents and injuries during accidents on elevators of the Committee for Analytics and Statistics of the National Elevator Union. The analysis of accidents on elevators with the injury to life or health of victims. The causes of injuries and deaths were identified and systematized. Ways are developed to increase the safety of elevators during their operation and maintenance and to reduce the severity of the consequences of accidents.